Barriers and strategies for better safety practices: the case of construction SMEs in Malaysia (Construction Economics and Building, 2019)
Despite the various efforts that have been made by the government and construction authorities to strengthen safety practices among SMEs in Malaysia, the construction SMEs are still unable to demonstrate good safety practices. As part of a wider intervention study to improve the safety practices of the SMEs, this study has taken the first step in identifying the barriers and strategies to improve the safety practices at construction sites in Malaysia. The study has been conducted using various approaches (workshops, site observation and questionnaire survey) that have enabled the triangulation of information. The findings highlighted that the main barriers to good safety practices are the implementation costs, poor safety culture and lack of safety commitment from the client. The proposed solutions include introducing safety as one of the construction KPIs, creating more safety-conscious culture and establishing a funding mechanism to support the cost of safety training. Subsequently, several recommendations have been provided by collating inputs based on the barriers, strategies and drivers through three-party collaboration (authorities, industry and academia) in creating  a collaborative movement towards enhancing safety practices among the SMEs. The fresh insights from this study would enable authorities and SMEs to be more proactive, rather than reactive in improving safety practices in the construction industry.